Understanding of Political Culture in Citizen of Muslimat NU in East Java - Ishomuddin Ishomuddin (el Harakah: Jurnal Budaya Islam, 2019)
In the context of its activities, since the NU Muslimat was established, it was almost all the archipelago had the same activities called religious activities, which included (1) manaqiban (2) dibaan, (3) reboan, (3) Muslimat Hajj Association and, (4) recitations with themes around the pillars of Islam. But there is a phenomenon of shifting understanding of the elite and NU Muslimat members to the themes of recitation and the movement of political da’wah, especially at the place where the research was conducted. The activities at NU Muslimat carried out not only as a routine activity of the Muslim community but also for the wider role of the NU Muslimat in general and its members to occupy strategic positions in the government or legislative members. From the above phenomena, the objectives of this study are to understand the culture and political understanding of NU Muslimat citizens in East Java. This research was conducted using a qualitative approach. Data collection uses observation, interviews, and documents. Data analysis was carried out using the Interactive Analysis Model of Miles, et al.Dalam konteks kegiatannya, sejak Muslimat NU didirikan memiliki kegiatan yang sama yang disebut kegiatan keagamaan, yang meliputi (1) manaqiban (2) dibaan, (3) reboan, (3) Ikatan Haji Muslimat , (4) kegiatan pengajian dengan tema seputar rukun Islam. Tetapi ada fenomena pergeseran pemahaman elit dan anggota Muslim NU dari kegiatan-kegiatan di atas ke tema-tema gerakan dakwah politik, terutama di tempat di mana penelitian dilakukan. Kegiatan-kegiatan Muslimat NU yang telah dilakukan tidak hanya sebagai kegiatan rutin, tetapi untuk peran yang lebih luas dari Muslimat NU pada umumnya dan anggotanya untuk menduduki posisi strategis di pemerintahan atau anggota legislatif. Dari fenomena di atas, tujuan dari penelitian ini adalah sebagai berikut: untuk memahami budaya dan pemahaman politik pada warga Muslimat NU di Jawa Timur. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif. Pengumpulan data menggunakan observasi, wawancara, dan dokumen. Analisis data dilakukan dengan menggunakan Model Analisis Interaktif Miles, Hubermen, Saldhana.